Effects of New Bayesian Penalized Likelihood Reconstruction Algorithm on Visualization and Quantification of Upper Abdominal Malignant Tumors in Clinical FDG PET/CT Examinations - Tatsumi, Mitsuaki; Soeda, Fumihiko; Kamiya, Takashi; Ueda, Junpei; Katayama, Daisuke; Matsunaga, Keiko; Watabe, Tadashi; Kato, Hiroki; Tomiyama, Noriyuki (Frontiers in Oncology, 2021)
Purpose: This study evaluated the effects of new Bayesian penalized likelihood (BPL) reconstruction algorithm on visualization and quantification of upper abdominal malignant tumors in clinical FDG PET/CT examinations, comparing the results to those obtained by an ordered subset expectation maximization (OSEM) reconstruction algorithm. Metabolic tumor volume (MTV) and texture features (TFs) as well as SUV-related metrics were evaluated to clarify the BPL effects on quantification. Materials and Methods: A total of 153 upper abdominal lesions (82 liver metastatic and 71 pancreatic cancers) was included in this study. FDG PET/CT images were acquired with a GE Discovery 710 scanner equipped with a time-of-flight system. Images were reconstructed using OSEM and BPL (beta 700) algorithms. In 58 lesions <1.5 cm in greatest diameter (small lesion group), visual image quality of each lesion was evaluated using a 4-point scale. SUVmax was obtained for quantitative metrics. Visual scores and SUVmax were compared between OSEM and BPL images. In 95 lesions > 2.0 cm in greatest diameter (larger lesion group), SUVmax, SUVpeak, MTV, and 6 TFs were compared between OSEM and BPL images. In addition to the size-based analyses, an increase of SUVmax with BPL was evaluated according to the original SUVmax in OSEM images. Results: In a small lesion group, both visual score and SUVmax were significantly higher in the BPL than OSEM images. The increase in visual score was observed in 20 (34%) of all 58 lesions. In a larger lesion group, no statistical difference was observed in SUVmax, SUVpeak, or MTV between OSEM and BPL images. BPL increased high gray-level zone emphasis and decreased low gray-level zone emphasis among 6 TFs compared to OSEM with statistical significance. No statistical differences were observed in other TFs. SUVmax-based analysis demonstrated that BPL increased and decreased SUVmax in lesions with low (<5) and high (>10) SUVmax in original OSEM images, respectively. Conclusion: This study demonstrated that BPL improved conspicuity of small or low-count upper abdominal malignant lesions in clinical FDG PET/CT examinations. Only 2 TFs represented significant differences between OSEM and BPL images of all quantitative metrics in larger lesions.